Effect of gasifying agents on sawdust gasification in a novel pilot scale bubbling fluidized bed system. (1st August 2019) - Meng, Fanbin; Ma, Qingbang; Wang, Hongde; Liu, Yueyang; Wang, Donghai
Highlights: A novel pilot scale bubbling fluidized bed gasification system was developed. Air, oxygen-enriched air, air-steam, and oxygen-steam was used as gasifying agents. Gasifying agents had a significant effect on gasification performance. The maximum value 1.44 of the H2 /CO ratio was found. Abstract: Effect of gasifying agents, such as air, oxygen-enriched air, air-steam, and oxygen-steam, on sawdust gasification was investigated in a novel pilot scale bubbling fluidized bed gasification system. The results showed that gasifying agents had a significant effect on gasification performance and producer gas properties. H2 content in the producer gas increased as equivalence ratio (ER) increased from 0.20 to 0.30 for all gasifying agents used. CO, CH4, and Cn Hm decreased and CO2 presented two different trends as ER increased from 0.20 to 0.30, resulting in lower heating value decreasing, gas yield increasing, carbon conversion efficiency and cold gas efficiency change. Compared to sawdust gasification using air only, oxygen-enriched air increased lower heating value due to reducing N2 dilution, air-steam favored H2 production because of enhancing water gas shift reaction, and oxygen-steam took both advantages of N2 free and steam addition. The maximum value of the H2 /CO ratio was 1.44 by using air-steam and oxygen-steam as the gasifying agents at the ER of 0.30.